Effects of Accurate and Inaccurate Feedback on Work Performance: The Role of the Awareness of Inaccuracy. Issue 1 (2nd April 2020) - Lee, Jidong; Lim, Sungjun; Oah, Shezeen
ABSTRACT: This study compared the effects of accurate (i.e., contingent) and inaccurate (i.e., non-contingent) feedback on work performance under two different work conditions. Under one work condition, participants could clearly see the outcome of their performance (i.e., visible condition). Under the other condition, they could not clearly see the outcome of their performance (i.e., non-visible condition). One hundred and twenty participants were randomly assigned to four experimental conditions (i.e., accurate/visible, inaccurate/visible, accurate/non-visible, and inaccurate/non-visible) and asked to perform a simulated work task. The results indicated that inaccurate feedback was as effective as accurate feedback under the non-visible condition, but inaccurate feedback was less effective than accurate feedback under the visible condition.